Crime Prevention Function of Criminalistics (Academic Journal of Internal Affairs, 2021)
Criminalistics is, in essence, mainly a practical and – to a sm aller extent – theoretical science of criminal investigation, in other words, it is a branch of criminal sciences that explores, creates, systemizes and applies – within normative legal frames - means and methods for the detection (prevention) and proof of crime. This study analysis the crime prevention function and fields of criminalistics and shows up present and future potential criminalistic preventive possibilities, methods.
Keywords: face recognition; Bayes-analysis; crime prevention; electronic data